2004
DOI: 10.1210/jc.2003-030975
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Serum Glycodelin and Insulin-Like Growth Factor-Binding Protein-1 in Women with Polycystic Ovary Syndrome during First Trimester of Pregnancy

Abstract: The polycystic ovary syndrome (PCOS) is associated with an increased rate of early pregnancy loss (EPL). Hyperinsulinemia is an independent risk factor for EPL and has been found to decrease levels of glycodelin and IGF binding protein-1 (IGFBP-1), two major endometrial proteins. We hypothesized that serum glycodelin IGFBP-1 concentrations would be reduced in women with PCOS during the first trimester of pregnancy.Fasting serum insulin, glycodelin, and IGFBP-1 were measured, and oral glucose tolerance tests we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 45 publications
5
64
0
3
Order By: Relevance
“…One study 36 reported that insulin reduction with metformin enhances uterine vascularity and reduces uterine vascular resistance, as demonstrated by a 20% reduction in vascular resistance in spiral arteries after metformin use (0.71 ± 0.02 to 0.57 ± 0.03 (p<0.001). This double-blind, placebo-controlled study of 48 women with PCOS also found that insulin reduction with metformin significantly increased follicular and luteal phase serum glycodelin and IGFBP-1 concentrations, two endometrial proteins necessary for implantation and adequate endometrial development that is reduced during the first trimester in women with PCOS 37 .…”
Section: Hypothesis: Insulin Resistance With Hyperinsulinemia As a Unmentioning
confidence: 77%
See 1 more Smart Citation
“…One study 36 reported that insulin reduction with metformin enhances uterine vascularity and reduces uterine vascular resistance, as demonstrated by a 20% reduction in vascular resistance in spiral arteries after metformin use (0.71 ± 0.02 to 0.57 ± 0.03 (p<0.001). This double-blind, placebo-controlled study of 48 women with PCOS also found that insulin reduction with metformin significantly increased follicular and luteal phase serum glycodelin and IGFBP-1 concentrations, two endometrial proteins necessary for implantation and adequate endometrial development that is reduced during the first trimester in women with PCOS 37 .…”
Section: Hypothesis: Insulin Resistance With Hyperinsulinemia As a Unmentioning
confidence: 77%
“…In a double blind, placebo-controlled study 36 of 48 women with PCOS, we demonstrated that the insulin-sensitizer metformin significantly increased follicular and luteal phase serum glycodelin and IGFBP-1 concentrations. In another study 37 , we evaluated 72 women with PCOS and 62 normal controls during the first trimester of pregnancy, and reported that both serum glycodelin and IG-FBP-1 concentrations were markedly and significantly lower in women with PCOS. Serum glycodelin was 56% lower in women with PCOS during gestational weeks 3-5, 23% lower during weeks 6-8, and similar by weeks 9-11.…”
Section: Obesitymentioning
confidence: 99%
“…In such conditions, subnormal glycodelin concentrations have been reported in endometrium, uterine flushings and serum at the time of expected endometrial receptivity (82)(83)(84)(85). Both glycodelin mRNA and protein are downregulated in human first trimester miscarriage (86), and pregnant women with polycystic ovary syndrome (PCOS), who subsequently miscarry show subnormal rise of glycodelin serum concentration during the first trimester, compatible with weaker placentation (87). As women with PCOS may have insulin resistance, it is not surprising that treatment with metformin has been found to increase glycodelin serum concentration in non-pregnant women with PCOS (88).…”
Section: Conditions Related To Implantation and Placentation Failurementioning
confidence: 99%
“…The treatment with metformin is also able to improve uterine vascularization in PCOS patients (Palomba et al 2006). In addition, metformin prevents early embryo resorption in women with PCOS (Jakubowicz et al 2004) by regulating both the PG and NO systems (inducible and constitutive nitric oxide synthase activity), the expression of progesterone-induced blocking factor, and the production of cytokines (Luchetti et al 2008). Thus, our second objective was to investigate the action of metformin in preventing the ovarian dysfunctions produced by hyperandrogenism.…”
Section: Introductionmentioning
confidence: 99%